2014
DOI: 10.1103/physrevb.89.075406
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent scanning tunneling spectroscopy on the Si(557)-Au surface

Abstract: Room-temperature and low-temperature (77 K) scanning tunneling spectroscopy (STS) and voltage-dependent scanning tunneling microscopy (STM) data are used to study the local electronic properties of the quasi-one-dimensional Si(557)-Au surface in real space. A gapped local electron density of states near theΓ point is observed at different positions of the surface, i.e., at protrusions arising from Si adatoms and step-edge atoms. Within the gap region, two distinct peaks are observed on the chain of localized p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Otherwise, this surface remains metallic at low temperature, i.e., no metal insulator transition and/or periodic lattice distortion have been observed as a function of temperature. 41 Here, we describe experiments that aim at the modification of the electronic properties of this atomic wire system by adsorption of atomic hydrogen. Compared with Si(553)−Au, higher chemical reactivity and interaction complexity are expected since the terraces are larger and Si adatom and restatom chains with unsaturated dangling bonds exist.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, this surface remains metallic at low temperature, i.e., no metal insulator transition and/or periodic lattice distortion have been observed as a function of temperature. 41 Here, we describe experiments that aim at the modification of the electronic properties of this atomic wire system by adsorption of atomic hydrogen. Compared with Si(553)−Au, higher chemical reactivity and interaction complexity are expected since the terraces are larger and Si adatom and restatom chains with unsaturated dangling bonds exist.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A restatom band crosses the Fermi level with an extremely flat slope close to the Γ point, and is thus less relevant in plasmon spectroscopy. Otherwise, this surface remains metallic at low temperature, i.e., no metal insulator transition and/or periodic lattice distortion have been observed as a function of temperature …”
Section: Introductionmentioning
confidence: 99%
“…Often, however, little is known about the structure of these underlying surfaces [4]. Among others, the Si(111) surface inclined by 10 • towards the [112] direction has been widely used for the formation of ordered nanostructures [4,6,8,9]. Based on scanning tunneling microscopy (STM) images Kirakosian et al reported that this vicinal Si(111) surface has the (557) orientation, with the period of the staircase being 5.73 nm, which correspond to 17 atomic rows [1].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Among such structures, monoatomic wires are candidates of interesting electronic properties such as Luttinger-liquid behavior. 8 The vicinal Si(111) surface with 10 • miscut towards the [1 1 1 1 2] direction is a popular stepped surface that can be used as a model system.…”
mentioning
confidence: 99%
“…Stepped well-ordered surfaces and, in particular, vicinal semiconductor surfaces, are well-suited for applications as nanotemplates for the fabrication of 1D nanostructures. Among such structures, monatomic wires are candidates of interesting electronic properties such as Luttinger-liquid behavior . The vicinal Si(111) surface with 10° miscut toward the [1̅ 1̅ 2] direction is a popular stepped surface that can be used as a model system.…”
mentioning
confidence: 99%